Can Bilirubin Be An Indicator For Predicting Coronary Artery Disease? - Fariba Nabatchian; Nahid Einollahi; Mohammad Ali Boroomand; Sakineh Abbasi (Tehran University of Medical Sciences, 2013)
Background and Aim: Oxidative interactions such as the formation of oxygen, peroxy radicals and LDL-cholesterol oxidation are involved in the development of atherosclerosis process. This study aims to examine the relationship between serum bilirubin levels and the incidence of coronary artery disease.Materials and Methods: Eighty-five patients and ninety-two healthy volunteers were enrolled in this study. Total and direct bilirubin levels were measured using diazo method. Besides, triglycerides and total cholesterol were determined by enzymatic method, HDL-Cholesterol by polyanionic method, and LDL-Cholesterol by direct method. For statistical analysis of data, SPSS 17 was applied. For qualitative variables, Chi-square and for quantitative variables, t-student tests were used. The significance level was set at P=0.05.Results: Direct, indirect and total bilirubin levels were 0.213, 0.375, 0.588 mg/dl for control group and 0.228, 0.365, 0.593 mg/dl for patient group, respectively. No significant difference was observed between the mean values for direct, indirect and total bilirubin in the two groups. Furthermore, there was no significant difference between triglycerides and total cholesterol level figures in the two groups. However, there was a significant difference between HDL-Cholesterol levels (P=0.001), smoking (P=0.031), family history (P=0.006), and mean blood pressure (P<0.001) of the two groups.Conclusion: The results of this study indicate that measurement of bilirubin as a marker for predicting coronary artery disease may be important. In the end, it should be mentioned that the findings of this study are consistent with some previous studies, but incompatible with others in this area.